2011
DOI: 10.1111/j.1365-2672.2011.04981.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactobacillus strains from Kimchi inhibits atopic dermatitis in NC / Nga mice

Abstract: Aims:  Atopic dermatitis (AD) is marked by elevated levels of immunoglobulin E and skin lesions such as oedema and haemorrhage. Kimchi is a Korean fermented food that contains beneficial bacteria for human health. In this study, Lactobacillus plantarum CJLP55, CJLP56, CJLP133 and CJLP136 isolated from Kimchi were investigated for their capacity to inhibit AD. Methods and Results:  The three strains, CJLP55, CJLP133 and CJLP136, suppressed AD‐like skin lesions, high serum IgE levels and epidermal thickening. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 23 publications
2
55
0
2
Order By: Relevance
“…Lactobacilli isolated from Kimchi inhibit atopic dermatitis, probably by altering the balance of Th1/Th2 ratio or inducing IL-10 production. 60 A new synbiotic, Lactobacillus casei subsp casei together with dextran, reduces the development of atopic dermatitis-like skin lesions in NC/Nga mice. This synbiotic combination significantly decreased clinical skin severity scores induced by picryl chloride and total IgE levels in sera of NC/Nga mice.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Lactobacilli isolated from Kimchi inhibit atopic dermatitis, probably by altering the balance of Th1/Th2 ratio or inducing IL-10 production. 60 A new synbiotic, Lactobacillus casei subsp casei together with dextran, reduces the development of atopic dermatitis-like skin lesions in NC/Nga mice. This synbiotic combination significantly decreased clinical skin severity scores induced by picryl chloride and total IgE levels in sera of NC/Nga mice.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Although the pathogenesis of AD is complicated, infiltration of immune cells such as mast cells, neutrophils, eosinophils, and lymphocytes are elevated in disease state [1]. In addition, serum immunoglobulin E (IgE) levels are elevated in AD [2].…”
Section: Introductionmentioning
confidence: 99%
“…L. rhamnousus JB-1, could attenuate an allergen induced allergic airway response in adult mice (Forsythe et al, 2007;Karimi et al, 2009) and others have since confirmed these antiallergic effects in the airway using a variety of bacteria (Lim et al, 2009;Adam et al, 2010;Li et al, 2010). In addition, several strains of lactobacillus have been shown to attenuate allergic dermatitis when administered orally to mice (Inoue et al, 2007;Hacini-Rachinel et al, 2009;Won et al, 2011). A number of mechanisms have been identified that may contribute to the ability of these bacteria to attenuate allergic inflammation including altered antigen presentation by dendritic cells Stagg et al, 2004), Th1 polarization (Adel-Patient et al, 2005;Hisbergues et al, 2007) or the induction of regulatory T cells (Karimi et al, 2009(Karimi et al, , 2012.…”
Section: Mast Cell Suppression By Beneficial Microbesmentioning
confidence: 89%